Hydroelastic and hydrodynamic analysis of a uniform rigid and flexible barge using weakly compressible smoothed particle hydrodynamics (WCSPH) - Ramli, Muhammad Zahir; Temarel, P.; Tan, M. (2018)
During fluid-structure interaction (FSI) fluid forces acting on the structure result in the structure moving and deforming, which in turn affects the flow boundary conditions, hence fluid motion. This interaction, also known as two-way coupling, has been studied in marine, offshore and coastal engineering. The majority of approaches used are based on potential flow where nonlinear effects are either ignored or allowed for through various assumptions on the body and free surface boundary conditions, leading to a range of partly to fully nonlinear methods. However, numerical models based on potential flow theory are unable to deal with extreme free surface deformations, as well as FSI problems where the effects of viscosity, turbulence and compressibility are significant. In order to address such shortcomings, there have been several attempts to solve nonlinear rigid body FSI and benefitting from rapid progress in Reynolds-averaged Navier-Stokes (RANS) code development, using either the finite difference method (FDM) or the finite volume method (FVM). However, most of these methods are Eulerian and, by and large, ineffective in the case of extreme events of wave breaking and water spray. Therefore, Lagrangian meshless methods are viewed as alternatives in providing accurate numerical solutions to improve inadequacy of mesh-based discretization. Smoothed Particle Hydrodynamics (SPH) is a mesh-free, Lagrangian method whereby the computational domain is represented by a set of interpolation points called particles where the fluid medium is discretised by the interaction between particles rather than grid cells. Each particle carries an individual mass, velocity, position and any other requisite physical characteristics, which evolve over time through the governing equations. All particles have a kernel function to define their range of interaction, while the hydrodynamic variables are defined by integral approximations. The current works presented are the first step in extending the application of WCSPH (weakly compressible SPH) to simulate two-way coupling in FSI. Numerical predictions for such interactions involving rigid and elastic body could provide useful knowledge in the possibility of implementing particle method in FSI. In the first part, WCSPH is applied to simulate rigid body motion of barge in regular waves. Vertical displacements of barge under different wave conditions are calculated and their Response Amplitude Operators (RAOs) and vertical bending moments (VBMs) are determined. Results are then compared to experimental data and 2 other numerical data. Secondly, forced oscillation tests are performed on a uniform flexible barge using WCSPH for the 3D radiation problem. Hydrodynamic coefficients, namely added mass and damping coefficients, are obtained for the rigid body motions of heave and pitch, and the 2-node (2VB) and 3-node (3VB) symmetric distortion mode shapes, including coupling terms. These are compared with potential flow (using 3D hydroelasticity) and RANS (using STAR-CCM+) predictions. Domain size, particle numbers and damping zones are modified based on different frequencies of oscillation, allowing the free surface to be well captured by WCSPH.